2022
DOI: 10.1002/cctc.202200190
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Water‐Gas Shift Reaction over Nickel‐Based Catalysts

Abstract: Recent advances in supported nickel catalysts for the water-gas shift (WGS) reaction are reviewed, focusing on the structuremechanism relationships. The WGS reaction can proceed via the redox, carboxyl, and formate pathways over the supported nickel catalysts. However, a discrepancy exists between the mechanism-level understanding and catalyst design principles in literature. In this review, we summarized the mechanismstructure relationship of nickel-based catalysts, emphasizing the effects of the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 155 publications
0
5
0
Order By: Relevance
“…The high CO 2 selectivity suggests that the WGS reaction (eqn (2)) and CO hydrogenation (reverse reaction of eqn (1)) occurred because these reactions increase CO 2 gas or decrease CO gas. It is known that both reactions are favourable thermodynamically at lower temperatures 55,59,60 and can proceed at lower temperatures (573–673 K) 55,61,62 on Ni/SiO 2 compared to SRM (eqn (1)). 7,8 To confirm the effect, we performed the thermal WGS and CO hydrogenation reactions on the Ni-Car sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high CO 2 selectivity suggests that the WGS reaction (eqn (2)) and CO hydrogenation (reverse reaction of eqn (1)) occurred because these reactions increase CO 2 gas or decrease CO gas. It is known that both reactions are favourable thermodynamically at lower temperatures 55,59,60 and can proceed at lower temperatures (573–673 K) 55,61,62 on Ni/SiO 2 compared to SRM (eqn (1)). 7,8 To confirm the effect, we performed the thermal WGS and CO hydrogenation reactions on the Ni-Car sample (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) occurred because these reactions increase CO 2 gas or decreases CO gas. It is known that both reactions are favoured thermodynamically at lower temperatures 55,59,60 and can proceed at lower temperatures (573-673 K) 55,61,62 on Ni/SiO 2 than those for SRM (Eq. 1) 7,8 .…”
Section: Comparison Between Ptsrm and Tsrmmentioning
confidence: 99%
“…9−11 Ceria has been widely used as an oxide support for metal catalysts in numerous heterogeneously catalyzed processes due to its remarkable oxygen storage and release abilities. Ceria-supported Ni and Cu catalysts have been widely used in the water−gas shift reaction, 12,13 reverse water−gas shift reaction, 14 direct conversion of methane to methanol, 15 and selective hydrogenation of acetylene. 16 Recent studies have found that the catalytic reactivity of ceria-supported metal nanoparticles is easily influenced by the properties of each component in the catalysts.…”
mentioning
confidence: 99%
“…Introducing a second metal, such as Cu or Au, to couple with Ni is an effective approach for improving the catalyst stability against coke formation and sintering while maintaining and in some cases promoting the catalytic activity. Ceria has been widely used as an oxide support for metal catalysts in numerous heterogeneously catalyzed processes due to its remarkable oxygen storage and release abilities. Ceria-supported Ni and Cu catalysts have been widely used in the water–gas shift reaction, , reverse water–gas shift reaction, direct conversion of methane to methanol, and selective hydrogenation of acetylene . Recent studies have found that the catalytic reactivity of ceria-supported metal nanoparticles is easily influenced by the properties of each component in the catalysts. A bimetallic Ni–Cu system exhibits unique properties compared to those of individual Ni and Cu counterparts due to the synergistic effects between the two metals and the interaction between the metal and oxide. , The properties of Ni–Cu alloys have been extensively studied for their potential application in several reactions. However, the detailed interactions among Ni, Cu, and ceria are not well understood, which makes the investigation of the geometric and electronic structures of ceria-supported Ni–Cu bimetallic surfaces of great scientific interest in the catalysis community.…”
mentioning
confidence: 99%
“…Because of the equilibrium limit, CO in reformate gas cannot be completely converted into hydrogen by the multistage water-gas shift (WGS) reaction: CO + normalH 2 normalO CO 2 + normalH 2 This WGS equilibrium also influences the removal of CO in hydrogen purification process like preferential oxidation (PROX) reaction after activation of relevant molecules on/near the catalytic sites, even when operated at relatively low temperature. Thus, it is still needed to further eliminate the residual CO (e.g., ∼100 ppm) to make the hydrogen produced from steam reforming qualified for application (e.g., CO ≤ 1 ppm) in polymer electrolyte membrane fuel cells (PEMFCs). …”
mentioning
confidence: 99%